Effective memory strategies used by adults to learn vocabulary in foreign language classes - Pradel, Sylwia (Humanities & Social Sciences Reviews, 2024)
Research objective: The aim of this article is to present three memory strategies such as grouping, using imagery, and placing new words into a context as effective tools while learning vocabulary by visual adult learners in a foreign language classes. Methodology: The whole research was experimental with the pretest and posttest as a tool for data gathering. As subjects of the research the second (experimental group) and third grade students (control group) of an extramural secondary school were chosen. Both groups consisted of ten randomly assigned learners who were in the 20-50 age group. Moreover, they were mostly pre-intermediate students. Main conclusions: After conducting the experiment it turned out that eight out of ten students from the experimental group achieved better results in the posttest compared to the ones from the control group. The mean of the experimental group was 17 percent higher in comparison with the control group. Application of the study: The presented articles shows three memory strategies used by learners in a foreign language classes. The conducted experiment has proved that these memory strategies are useful and effective, especially if they are adequately linked with learning styles and other factors that may affect the strategy use. Originality/Novelty of the study: In the future research the issue of using memory strategies by visual learners should be explored further. Researchers may focus their attention on other memory strategies. There is also a need to broaden research beyond the adults and pay more attention to younger learners as well as those with learning disabilities to see how memory strategies can assist them.